1987
DOI: 10.1055/s-0038-1651088
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Factor Xllla Activity on Human Whole Blood Clot Lysis In Vitro

Abstract: SummaryWe studied the influence of Factor XIII a (F XIII a) activity on the lysis rate of fresh whole human blood clots, without using anticoagulants. Clotting was induced by exogenous thrombin, lysis by tissue-type Plasminogen Activator (t-PA) added before clotting. After various periods of time, lysis rates were determined by measuring the radioactivity in the supernatant of the clot originating from 125I-Fibrinogen added before clotting.Lysis rates were determined in the presence of endogenous F XHIa and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 25 publications
2
36
0
1
Order By: Relevance
“…In vitro studies suggest that fibrin-cross-linked ␣2-antiplasmin is an important determinant of the susceptibility of plasma clots to fibrinolysis. 21,25,27 In fact, Jansen et al 27 concluded that while factor XIIIa-mediated cross-linking inhibited fibrinolysis, its major inhibitory effect was mediated through the cross-linking of ␣2-antiplasmin to fibrin. In contrast, Francis and Marder, 26 in studies of supraphysiological doses of factor XIII, concluded that fibrin-fibrin cross-linking in and of itself contributes to fibrinolytic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies suggest that fibrin-cross-linked ␣2-antiplasmin is an important determinant of the susceptibility of plasma clots to fibrinolysis. 21,25,27 In fact, Jansen et al 27 concluded that while factor XIIIa-mediated cross-linking inhibited fibrinolysis, its major inhibitory effect was mediated through the cross-linking of ␣2-antiplasmin to fibrin. In contrast, Francis and Marder, 26 in studies of supraphysiological doses of factor XIII, concluded that fibrin-fibrin cross-linking in and of itself contributes to fibrinolytic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-linking by FXIIIa improves the mechanical strength, rigidity and elasticity of the clot and increases its resistance to fibrinolysis [11][12][13][14][15][16]. Inhibition of FXIIIa activity enhances fibrin degradation mediated by plasmin in vitro [17] and accelerates thrombolysis in animal models of venous and arterial thrombosis and in experimental pulmonary embolism [18][19][20].…”
Section: Fxiiia-i Induced Cross-l Linking Reactions In the Fibrin Clomentioning
confidence: 99%
“…Inhibition of the binding of α2-PI to fibrin considerably accelerates the lysis of the clot [17,40,41]. α2-PI mutated at its active site also enhanced fibrin degradation [42].…”
Section: Fxiiia-i Induced Cross-l Linking Reactions In the Fibrin Clomentioning
confidence: 99%
“…Subsequent studies in whole blood and plasma showed that the formation of fibrin-fibrin crosslinks do not contribute significantly to the resistance of the clot to fibrinolysis, and thus that the stability of thrombi to lysis depends predominantly on crosslinking of a2AP into the thrombus. 32,33 Other studies showed that a2AP may also noncovalently bind to fibrin and fibrinogen, which could potentially serve to provide the proper orientation of the crosslinking sites of a2AP and fibrin to facilitate crosslinking of a2AP to fibrin. …”
mentioning
confidence: 99%